Answer:
3 plus 4. and 2 plus 1. or 4 plus 3 or 1 plus 2
Step-by-step explanation:
Try breaking these into sections.
Twice: 2 times
The sum of: add
A number: choose a variable, like x
---Thus "the sum of a number and 4" becomes "add x and 4" which, mathematically, is "x+4"
-----Continuing to put it all together, "Twice the sum of a number and four" becomes "2 times (x+4)" which, mathematically, is "2(x+4)"
Is: equals
-------"Twice the sum of a number and four is" becomes "2(x+4)="
23 less than: subtract 23. This one tends to trick people; "23 less than" will become "__ - 23", NOT "23 - __"
three times the number: 3 times x
---"23 less than three times the number" becomes "subtract 23 from 3 times x" which, mathematically, is "3x-23"
-------So the final phrase: 2(x+4)=3x-23"
1: 11/28
2: 67/72
3: 1 11/30
You could do the question the way it is written, but it is far easier to bring the negative power up to the numerator.
y= x^2 - 3. The derivative of that is
dy/dx = 2x The three is a constant and is always dropped when a derivative is taken
d(-3)/dx = 0
If you are a purist and want to solve the question the way it is written, you could do it this way.
dy/dx = d(1)/dx x^-2 - d(x^-2)/dx * 1
======================
(x^-2)^2
dy/dx = - (-2 x^ - 3) / x^-4
dy/dx = 2 x^-3 * x^4
dy/dx = 2 x^(-3 + 4)
dy/dx = 2x ^ 1
dy/dx = 2x <<<<< answer
Answer:
asymptote
Step-by-step explanation: